DOSE ADJUSTMENT PRACTICES OF PEGINESATIDE VS. EPOETIN IN EMERALD 1 AND 2 PIVOTAL TRIALS - Amit Sharma; Whedy Wang; Alex Yang; Ali Hariri; Hong-Ye Gao; Anne-Marie Duliege; Krishna Polu; Nina Oestreicher (The Korean Society of Nephrology, 2012)
Peginesatide (P) is a synthetic, pegylated, peptide-based ESA approved for treatment of anemia due to chronic kidney disease in adult patients (pts) on dialysis. P demonstrated noninferiority to epoetin (E) in maintenance of Hb levels in hemodialysis (HD) pts in two Phase 3 randomized, active-controlled, open-label trials (EMERALD 1,2). A large dialysis organization (LDO) recently reported an ESA dose adjustment rate of 12.1/pt-year (Bond et al, ISPOR 2012). This post hoc analysis evaluated dosing practices for maintaining Hb with P vs E. Pooled data from the two trials compared P (1x monthly; N=1066) with E (1-3x wkly; N=542) in HD pts previously on stable doses of E. Hb was measured during screening, at baseline and wkly (evaluation period, wks 29-36) or every 2 wks (all other periods). Dose adjustments were not to be made more frequently than every 4 wks, unless required for safety purposes. Dose adjustments (defined as change >±20% from last dose) were evaluated during the titration (wks 0-28), evaluation, and long-term follow-up (LT, wks 36-52) periods. Dose postponements were defined as >35d for P; for E, they were >4d, 6d, or 9d for TIW, BIW, and QW, respectively. Across the entire study period, P doses were adjusted ∼3 times less frequently and held ∼8 times less than P (Table). P (per pt-year) E (per pt-year) E/P ratio Total Dose Adjustments 3.5 10.3 2.9 Dose Increases 1.7 5.3 3.0 Dose Decreases 1.8 5.0 2.8 Dost Postponements 0.6 5.0 8.3 Within each treatment arm, dose adjustment and postponement rates (including corresponding E/P ratios) were similar across titration, evaluation, and LT periods. E dose adjustment rate was similar to that of real world practice in an LDO. E doses were adjusted and held more frequently than P despite similar protocol specifications for dose alteration and Hb maintenance.